Perspective Drawings of Senior High School Students in Housekeeping and Technical Drafting: A Theory Development Approach (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
The study focused on senior high school students’ perspective drawings who are majoring in housekeeping and technical drafting of the Technical-Vocational Livelihood (TVL) Track. It is an attempt to develop a theory as well as formulated an academic strategic plan that will give students the advantage, they will need in making the transition from high school to college. The specific objectives are to explore the students’ images based on the drawings they have created and discover the aspects of perspective drawing as essential to a teacher’s presence. There were ten (10) informants in this study that has been systematically collected and analyzed. With the adapted lesson plan of Thrive Collective approach, the study utilized the grounded theory during data analysis with the following stages: open coding, axial coding, and selective coding. Subjects should understand what is being asked of them and involved persons must be competent to consent. From the conducted thematic analysis, three (3) propositions were drawn up: (a) when the students are interested in what they are doing, they will be able to perform the task effectively and efficiently; (b) students learn by imitating others on how they do things aided by technology, and (c) solving problems could be done gradually by using mental visual perceptions. From the propositions, these hypotheses were derived: (a) student’s ability could be recognized based on their drawings; (b) the power of students’ imagination could be put into practice, and (c) life skills are influenced by the students’ intellectual capacity with the guidance of the teachers. Considering these suppositions, students’ perspective drawings are brought by imagery in relation to real-world problems.